(untitled) (Research, Society and Development, 2022)
In the past years, with the emergence of the pandemic caused by COVID-19, the world population used different practices to survive, buy, work, study and others. Care for the virus eradication was and still is essential for the return of social activities. Specifically in the education field, the losses are being alarming, exemplified by students who are on the margins of educational practice. As a way to reduce the damage in education, digital information and communication technologies are used as an indispensable means for the “closeness” to take place between people in the most different spaces, whether in basic education or higher education. In this sense, the respective study analyzes the contribution of digital information and communication technologies to the teaching and learning process during the COVID-19 pandemic. The theme is relevant, as it is about the reality that involves the acts of teaching, learning, as well as researching. The methodological structure is qualitative and bibliographic according to the aforementioned authors. The results show that electronic devices such as computers, cell phones and televisions have become indispensable for the virtual educational meeting and that such technological resources have come to be widely used by the educational community to carry out classes and meetings. Therefore, there was a need to learn how to handle devices and applications. It is concluded that from these educational interactivities developed in current times, they can be in touch with the society in the intention of including different groups of citizens in the Brazilian context.